(untitled) (Research, Society and Development, 2020)
UTIs are infections usually caused by Gram-negative bacteria, mainly enterobacteria, commonly acquired in the community or in hospitals. The anatomical and physiological changes imposed into the urinary tract by pregnancy may predispose to the transformation of asymptomatic bacteriuric women on pregnant women with symptomatic UTIs, thus investigating the epidemiology of UTI (bacterial isolates and sensitivity to antibiotics) during pregnancy is key to guiding interventions. In the present study, it was aimed to investigate the presence of enterobacteria that cause bacteriuria and UTI in pregnant women in the city of São João do Triunfo-PR from 2015 to 2019. From 176 samples, we detected the presence of Escherichia coli in 95 (54%), of the clinical samples, Klebsiella sp. in 35 (19,9%), followed by Proteus sp. 29 (16,5%) and Enterobacter sp 17(9,6%). Concerning antimicrobial resistance, the highest rates of multiresistance were observed among Escherichia coli isolates, where 20% isolates were resistant to four or more antibiotics and 3,1% isolates were resistant to more than six antimicrobial agents. Klebsiella sp. were the most sensitive to the antimicrobials tested, 68,6% were sensitive to all the antibiotics studied. Infections caused by Escherichia coli were commonly related to high counts of colony-forming units (CFU), in which case 84,2% of samples were counted above 100,000 CFU/mL, while all samples positive for Klebsiella sp., Enterobacter sp. and Proteus sp. produced infections with counts below 100,000 CFU/mL. Our results demonstrate that Escherichia coli is the main enterobacterium that causes UTI in pregnant women, mainly through multi-drug resistance strains, whereas Klebsiella sp., Enterobacter sp. and Proteus sp. produced only bacteriuria.